Lessons from Little Rock - Roberts, Terrence (Butler Center Books, 2009)
Sober news reports of a U.S. Army convoy rumbling across the bridge into Little Rock cannot overpower this intimate, powerful, personal account of the integration of Little Rock Central High School. Showing what it felt like to be one of those nine students who wanted only a good high school education, Roberts's rich narrative and candid voice take readers through that rocky year, helping us realize that the historic events of the Little Rock integration crisis happened to real people-to children, parents, our fellow citizens.